IN SILICO ANALYSIS OF SAGA SEED EXTRACT (Abrus precatorius L.) FOR ANDROGENIC ALOPECIA TREATMENT - Dewi Rahmawati; Rizky Farmasita Budiastuti; Ashfar Kurnia (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2026)
Androgenic alopecia (AGA) is a genetically determined hair loss condition. In men, hair loss is influenced by androgen hormones, whereas in women, androgenic alopecia is thought to be influenced by genetic factors. Currently, several drugs are used in the treatment of AGA, including 5α-reductase inhibitors, minoxidil, finasteride, and dutasteride for androgen-related disorders. However, the use of these medications may cause various undesirable side effects, such as impotence, abnormal ejaculation, decreased ejaculate volume, sexual dysfunction, gynecomastia, testicular pain, reduced muscle growth, and severe myopathy. The use of natural products as hair growth agents has been widely investigated, and several herbal extracts have been reported to be effective in the management of androgenic alopecia, one of which is saga seed extract. Saga seeds have been reported to contain campesterol, cholesterol, palmitic acid, lignoceric acid, oleic acid, linoleic acid, linolenic acid, cycloartenol, beta-amyrin, β-sitosterol, stigmasterol, trigonelline, and brassicasterol (1)). This in silico study was conducted to evaluate the potential of β-sitosterol, stigmasterol, and brassicasterol present in saga (Abrus precatorius L.) seed extract compared with the positive control, minoxidil. Molecular docking analysis using Molegro Virtual Docker based on rerank score values demonstrated that brassicasterol exhibited better binding potential than β-sitosterol, stigmasterol, and the positive control minoxidil.